Measurement of dijet production in diffractive deep-inelastic ep scattering at HERA - Andreev, Vladimir; Huber, Florian; Herbst, Michael Clemens; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (Journal of high energy physics, 2015)
A measurement is presented of single- and double-differential dijet cross sections in diffractive deep-inelastic ep scattering at HERA using data collected by the H1 experiment corresponding to an integrated luminosity of 290 pb−1. The investigated phase space is spanned by the photon virtuality in the range of 4 < Q2< 100 GeV2 and by the fractional proton longitudinal momentum loss xℙ< 0.03. The resulting cross sections are compared with next-to-leading order QCD predictions based on diffractive parton distribution functions and the value of the strong coupling constant is extracted.